Data Mining Untuk Menganalisis Gagal Serah Dana Pada Transaksi Jual Beli Saham - Miranda, Eka; Yonathan, Hans; Lokanatha, Ivander G.; Suryawan, Josep Benedictus (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Competitive environment among investment firms encourage them to be able to conduct analysis related to investments activities with the potential failure of transfers’ funds. The purpose of this writing is to analyze the needs of the information required in the process of analysis the potential failure of funds transferring in a process of buying and selling stocks and using data mining techniques (Clustering) to support analysis process of the failure of fund transfrerring in a process of buying and selling stocks . Data collection methods used in this study consists of: Literature study, interviews and observations. While the implementation phase of data mining techniques consist of: Data Cleaning, Data Integration, Data Selection, Data Transformation, Data Mining, Pattern Evaluation and Knowledge Presentation. Data mining technique is used to analyze the data in order to know which transactions can lead to failed transfers funds and group them based on Receiving Failure. The clustering result will produce knowledge that is useful in the decision making especially to the top management level. The conclusions of this writing is using data mining techniques that have been designed in this writing, help the management take decisions with more precise so as to avoid losses for company.